Antidepressant activity of butterfly pea (Clitoria ternatea L.) flower infusion in male albino mice Mus musculus L. exhibiting depression-like behavior - Emi Suhaemi; Lutfi Maulana; Rarastoeti Pratiwi (Pharmaciana, 2026)
Depression is a mental disorder that affects thoughts, emotions, behavior, and physiological functions. Prolonged, untreated depression can lead to suicidal tendencies. Conventional antidepressant drugs often cause side effects and may lead to dependency. Butterfly pea (Clitoria ternatea L.) contains bioactive compounds that have potential antidepressant properties. This study aimed to analyze the antidepressant effect of butterfly pea flower infusion in male albino mice (Mus musculus Linnaeus, 1758) exhibiting depression-like behavior. The mice were divided into six treatment groups (n=4): a normal control (no repeated stress induction), a negative control (repeated stress induction), a positive control (repeated stress induction and administered fluoxetine 20 mg/kg BW), and three treatment groups receiving butterfly pea flower infusion at doses of 625, 1,250, and 2,500 mg/kg BW. Repeated stress was induced using the Tail Suspension Test (TST) for 10 minutes/day for 7 days, followed by evaluation of depression-like behavior by measuring immobility time using the Forced Swim Test (FST) for 6 minutes/day over 2 days. At the end of treatment period, blood samples were collected to measure glucose, total cholesterol, triglycerides, and corticosterone levels. The results showed that the infusion significantly reduced (p < 0.05) corticosterone and total cholesterol levels at doses of 1,250 and 2,500 mg/kg BW. However, it did not significantly reduce immobility time, blood glucose, or triglyceride levels.